Energy Saving Mechanisms for MAC Protocols in Wireless Sensor Networks. (2010) - Al Ameen Al Ameen, Moshaddique Moshaddique; Islam Islam, S. M. Riazul S. M. Riazul; Kwak Kwak, Kyungsup Kyungsup
Abstract : Energy efficiency is a primary requirement in a wireless sensor network (WSN). This is a major design parameter in medium access control (MAC) protocols for WSN due to limited resources in sensor nodes that include low battery power. Hence a proposed MAC protocol must be energy efficient by reducing the potential energy wastes. Developing such a MAC protocol has been a hot research area in WSN. To avoid wasting the limited energy, various energy saving mechanisms are proposed for MAC protocols. These mechanisms have a common design objective—to save energy to maximize the network lifetime. This paper presents a survey on various energy saving mechanisms that are proposed for MAC protocols in WSN. We present a detailed discussion of these mechanisms and discuss their strengths and weaknesses. We also discuss MAC protocols that use these energy saving mechanisms.